(untitled) (Journal of the College of Basic Education, 2022)
The relationship of the explosive force of the arms and the distinctive force of velocity for the two men with the performance of the skills of serving and spiking with volleyball The game of volleyball is a group sport that is characterized by difficult situations during performance, and therefore the players of this game must be characterized by the elements of physical fitness because it is considered an essential part in the success of any sports team and here are many physical characteristics, including (strength, speed, elongation, flexibility and agility) as well as many skillful qualities of them. (Scoring, patience, handling and deception) which have great importance to reach the best levels, we find that offensive skills in volleyball, including the skills of serving and hitting, as they need strength and speed, as these two skills play a major role in achieving the success and progress of the team and making it one of the advanced teams. It is necessary for any player to pay attention to this aspect, and the research aims to: 1- Knowing the correlation between the explosive force of the arms and the performance of the skill of serving and crushing volleyball in the research sample. 2- Knowing the correlational relationship between the force and the characteristic velocity of the two men and the performance of the skill of serving and crushing volleyball in the research sample. Hypothesis search: 1- There is a statistically significant correlation between the explosive power of the arms and the performance of the skill of serving and crushing volleyball in the research sample 2-There is a statistically significant correlation between the force characteristic of speed for the two men and the performance of the skill of serving and crushing volleyball in the research sample